RELIGIOUS VALUES AND SPIRITUAL NEEDS IN THE MODERN FAMILY: SOCIAL PHILOSOPHICAL ANALYSIS - Nishonovich, Tursunov Bakhodir (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study explores the relationship between religious values and spiritual needs in contemporary families, particularly the increasing conflict between traditional beliefs and societal changes. While religious values are recognized as essential for maintaining moral and social stability, limited attention has been given to how modern technological advancements and evolving social structures influence spiritual needs within families. Methods: A qualitative, socio-philosophical approach is employed to analyze historical texts, legal frameworks, and theoretical discussions. This method allows for an in-depth evaluation of how the role of religious values in family life has transformed over time in response to societal shifts. Results: Findings indicate that while religious traditions remain fundamental to family stability, increased exposure to digital culture and globalization leads to a decline in spiritual engagement among individuals. This disengagement contributes to family conflicts and identity crises. The study highlights the necessity of adapting religious values to align with evolving societal norms while preserving moral integrity within family life. Novelty: This research provides new insights into the intersection of religious values, spiritual needs, and modern technological influences on family dynamics. It emphasizes the importance of policy and educational initiatives in fostering an environment where spiritual well-being coexists with societal advancements, ultimately ensuring family cohesion amid rapid social transformations.